2020
DOI: 10.3389/fneur.2020.00324
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindles and Fragmented Sleep as Prodromal Markers in a Preclinical Model of LRRK2-G2019S Parkinson's Disease

Abstract: Sleep disturbances co-occur with and precede the onset of motor symptoms in Parkinson's disease (PD). We evaluated sleep fragmentation and thalamocortical sleep spindles in mice expressing the p.G2019S mutation of the leucine-rich repeat kinase 2 (LRRK2) gene, one of the most common genetic forms of PD. Thalamocortical sleep spindles are oscillatory events that occur during slow-wave sleep that are involved in memory consolidation. We acquired data from electrocorticography, sleep behavioral measures, and a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Further, in LRRK2 -PD, EDS and RBD are typically absent from the pre-symptomatic stages of the disease [ 184 , 266 ]. The sleep fragmentation observed in the preclinical murine LRRK2-G2019S model represents one of the four sleep complaints experienced by 56% of LRRK2-PD patients [ 184 , 267 ]. It remains to be shown whether the sleep fragmentation in these mice is specific for NREM or REM sleep as the study did not differentiate between sleep stages.…”
Section: Circadian and Sleep Phenotypes Of Murine Models Of Pdmentioning
confidence: 99%
“…Further, in LRRK2 -PD, EDS and RBD are typically absent from the pre-symptomatic stages of the disease [ 184 , 266 ]. The sleep fragmentation observed in the preclinical murine LRRK2-G2019S model represents one of the four sleep complaints experienced by 56% of LRRK2-PD patients [ 184 , 267 ]. It remains to be shown whether the sleep fragmentation in these mice is specific for NREM or REM sleep as the study did not differentiate between sleep stages.…”
Section: Circadian and Sleep Phenotypes Of Murine Models Of Pdmentioning
confidence: 99%
“…Studies in G2019S KI mice compared with WT controls ( Table 4 ) revealed no changes in spontaneous locomotion in motility cages at 5 months [ 62 ] or rotarod performance at 2 months [ 74 ]. On the other hand, G2019S KI mice outperformed WT controls in the OF and rotarod test at 6 months [ 63 , 81 , 70 ], a finding that, however, was not confirmed by more recent studies [ 64 , 71 ]. R1441C/G KI mice do not show differences in spontaneous locomotion or rotarod performance compared with WT counterparts up to 22 months [ 65 , 66 , 74 ].…”
Section: Motor Signsmentioning
confidence: 98%
“…Careful sleep analysis was carried out in 8–10-month-old G2019S KI mice [ 71 ] ( Table 4 ). These mice slept a similar amount of time as WT counterparts, but the number of sleep bouts was greater and their duration shorter, indicating sleep fragmentation.…”
Section: Non-motor Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the transgenic models, BAC-SNCA A53T mice display REM sleep without atonia, which is a key feature of REM sleep behaviour disorder, at as early as 5 months of age [ 67 ]. LRRK2 G2019S mice also display sleep problems, manifest as increased sleep fragmentation that reduces sleep quality [ 190 ]. However, despite the clear link between GBA mutations and REM sleep behaviour disorder in patients [ 191 ], there are no reports to our knowledge of altered sleep patterns in GBA mice.…”
Section: Modelling the Nmsmentioning
confidence: 99%